2003
DOI: 10.1521/aeap.15.1.5.7.23616
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk and Prevention Among Asian/Pacific Islander Men Who Have Sex With Men: Listen to Our Stories

Abstract: Despite increasing need for HIV prevention research and intervention programs, the voices and stories of Asian and Pacific Islander men who have sex with men (API MSM) have remained absent from HIV prevention literature. Five focus groups with API MSM (N = 38) were conducted to identify psychological, social, and cultural factors related to HIV risk and protection. Six themes were identified based on focus group discussion: (a) dual-identity status, (b) coming out and disclosure issues, (c) relationships and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 13 publications
0
71
1
Order By: Relevance
“…Sexual risk behaviors persist at high levels among APIs and new cases of HIV are rising in this group (Centers for Disease Control and Prevention, 2010). API MSM living in the United States have been reported to face significant challenges of low self-esteem and low self-efficacy owing to their dual minority status (Chng, Wong, Park, Edberg, & Lai, 2003;Han, 2008;Mao, Van de Ven, & McCormick, 2004;Nemoto et al, 2003). Choi, Yep, and Kumekawa (1998) have documented that API MSM usually suffer a high level of psychological distress because within API communities and families, homosexuality is highly stigmatized and typically not accepted, and because collectivistic API cultures place great importance on marriage and having children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual risk behaviors persist at high levels among APIs and new cases of HIV are rising in this group (Centers for Disease Control and Prevention, 2010). API MSM living in the United States have been reported to face significant challenges of low self-esteem and low self-efficacy owing to their dual minority status (Chng, Wong, Park, Edberg, & Lai, 2003;Han, 2008;Mao, Van de Ven, & McCormick, 2004;Nemoto et al, 2003). Choi, Yep, and Kumekawa (1998) have documented that API MSM usually suffer a high level of psychological distress because within API communities and families, homosexuality is highly stigmatized and typically not accepted, and because collectivistic API cultures place great importance on marriage and having children.…”
mentioning
confidence: 99%
“…Choi, Yep, and Kumekawa (1998) have documented that API MSM usually suffer a high level of psychological distress because within API communities and families, homosexuality is highly stigmatized and typically not accepted, and because collectivistic API cultures place great importance on marriage and having children. In addition, the conceptualization of masculinity in the United States has led some API MSM to perceive themselves as feminine and unattractive within both the mainstream American and gay communities (Han, 2008;Nemoto et al, 2003). As a consequence, the dominant negative attitudes about being gay and API create an environment that subjects API MSM to stress, depression and a low sense of self-worth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the availability of culturally competent HIV prevention programs specific to APIs is limited (Nemoto, Operario et al, 2003), the programs must address the target groups' specific needs and HIV risk behaviors. This study showed that a high proportion of the participants reported inconsistent condom use with casual partners in the past 6 months (44% of substance users, 60% of incarcerated participants for vaginal sex, and 26% of MSM for anal sex).…”
Section: Discussionmentioning
confidence: 99%
“…A study among Filipino amphetamine users showed that they faced risk for HIV through unprotected sex, sex while under the influence of drugs and alcohol, injection drug use, and low rates of HIV testing (Nemoto, Operario, & Soma, 2002). Previous studies (Nemoto et al, 1999;Nemoto, Operario et al, 2003) clearly showed that both API MSM and substance users who are not MSM engage in risky sexual behaviors and sex under the influence of substances. However, past research studies do not provide a clear picture on the prevalence of HIV risk behaviors in API communities because studies tended to focus on one specific risk group, either API MSM or substance users.…”
mentioning
confidence: 99%